(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The study aimed to investigate the hepatoprotective effects of Gastrodia elata rhizome (GR) on thioacetamide (TAA)-induced liver injury in dogs. We evaluated serum biochemical and hematological parameters, with emphasis on alanine transaminase (ALT), alanine phosphates (ALP), and nitric oxide (NO) levels, in dogs with TAA-induced liver injury. Materials and Methods: The animals were divided into a control group (Con), TAA group, Silymarin group (Sil, 50 mg/kg), Gastrodia rhizome low dose (GRL) (low) + TAA, GRH (high) + TAA, and GR high-dose group (GRH) control group. GRL and GRH were given daily at 50 and 100 mg/kg, respectively. TAA was given on days 1, 4, and 7 at a dose of 300 mg/kg. Results: GR significantly reduced liver injury in treated animals, as indicated by lowered levels of ALT (about 32% at day 21 in both GRL + TAA and GRH + TAA groups), ALP (about 17% and 21% at day 21 in both GRL + TAA, GRH + TAA groups, respectively), and NO (about 36% at day 21 in both GRL + TAA, GRH + TAA groups) compared to the TAA control group. Hematological parameters showed mild changes during the experiment. High-performance liquid chromatography analysis revealed gastrodin, a major component of the GR extract, constitutes 2.6% of the extract. Conclusion: The GR demonstrated significant hepatoprotective effects against TAA-induced liver injury in dogs. The study provides evidence for the potential therapeutic use of GR in the management of liver diseases. J. Adv. Vet. Anim. Res., 10(2): 144–150, June 2023 http://doi.org/10.5455/javar.2023.j663